ANALISIS MAKNA SIMBOL FISIKA PADA MATERI USAHA DAN ENERGI DARI PERSPEKTIF BAHASA INDONESIA - Donna Beata Felisitas Marbun; Jeonery Benediktus Sembiring; Sesilia Anju Chrystina Tamba; Chyntia Anne Napitupulu; Nurul Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the meaning of physics symbols in the topic of work and energy from the perspective of the Indonesian language and to determine their influence on students’ conceptual understanding in physics learning. The background of this research is based on the low level of students’ understanding of physics symbols, which often leads to misconceptions in the topic of work and energy. Physics symbols such as work (W), energy (E), force (F), and displacement (s) are frequently understood only as mathematical formulas without comprehending their actual conceptual meanings. This research employed a literature review method with a descriptive qualitative approach. The data were obtained from various written sources, including physics textbooks, scientific journals, research articles, learning modules, and other academic references related to work and energy as well as the use of scientific language in physics. Data collection techniques were carried out through reading, understanding, noting, and classifying relevant information from the literature sources. Data analysis was conducted through the stages of data collection, data classification, data interpretation, and conclusion drawing. The results of the study indicate that physics symbols play an important role as representations of scientific language in physics learning. However, differences in meaning between everyday language and scientific language often cause students to misinterpret the concepts of work and energy. In addition, learning that focuses too much on mathematical problem-solving also contributes to students’ low conceptual understanding. Therefore, more contextual, interactive, and concept-oriented learning approaches are needed to improve students’ understanding of the meaning of physics symbols in learning physics.